Angioid streaks of the retina (Ukrainian Journal of Ophthalmology, 2025)
This paper is a review of the current literature on the etiology, pathogenesis, clinical picture and treatment of angioid streaks of the retina. Angioid streaks (AS) are a disease of the fundus characterized by cracks in the thickened, calcified and abnormally brittle collagenous and elastic layers of the Bruch's membrane;  in up to 50% of cases, associated with a systemic condition, most commonly pseudoxanthoma elasticum (PXE), Paget's disease of bone, and etc. Various diagnostic techniques (visual acuity testing, refractometry, tonometry, slit-lamp examination of the anterior segment, ophthalmoscopy, retinal fluorescein angiography (FA) and optical coherence tomography (OCT)) are used for the diagnosis, assessment, and monitoring of the disease. Choroidal neovasculatization (CNV) is the most common complication leading to reduced vision. Intravitreal anti- vascular endothelial growth factor administration is currently the most effective treatment for CNV.
Keywords: angioid streaks; choroidal neovascularization; intravitreal administration